Increased Mast Cell Counts and Degranulation in Microscopic Colitis - Zhikai Chi; Jing Xu; Romil Saxena (Gastroenterology Research and Practice)
Objectives. Microscopic colitis (MC) is characterized by chronic diarrhea, normal colonoscopy findings, and mucosal inflammation in colonic biopsies and can be classified as collagenous colitis (CC) or lymphocytic colitis (LC). However, the pathogenesis of MC is largely unknown. In this study, we aimed to study mast cell counts and activation in MC. Methods. We investigated 64 biopsy samples from the surgical pathology database of Indiana University Health, which met the diagnostic criteria for CC or LC along with 20 control samples collected from 2014 to 2015. The specimens were used for the quantification of mast cells by examining the presence of intracellular and extracellular tryptase by immunohistochemistry. Results. In the lamina propria, the mast cell count was higher in both CC and LC groups than the control (mean highest count, 39/high-power field (HPF) vs. 30/HPF vs. 23/HPF; P<0.01). Extracellular tryptase was present in 10% of control subjects as compared to 41% of CC (P<0.05) and 60% of LC (P<0.001) patients. When LC patients were stratified into two groups with either <80% or >80% of fragments affected by inflammation, increased mast cell counts are only observed in the >80% involvement group compared with the control, but not the <80% involvement group. Conclusions. The increased mast cell count and degranulation are identified in MC, suggesting that mast cell activation might be involved in the pathogenesis of MC.